Classic and Novel Sex Hormone Binding Globulin Effects on the Cardiovascular System in Men. (21st July 2021) - Basualto-Alarcón, Carla; Llanos, Paola; García-Rivas, Gerardo; Troncoso, Mayarling Francisca; Lagos, Daniel; Barrientos, Genaro; Estrada, Manuel
Abstract : In men, 70% of circulating testosterone binds with high affinity to plasma sex hormone binding globulin (SHBG), which determines its bioavailability in their target cells. In recent years, a growing body of evidence has shown that circulating SHBG not only is a passive carrier for steroid hormones but also actively regulates testosterone signaling through putative plasma membrane receptors and by local expression of androgen-binding proteins apparently to reach local elevated testosterone concentrations in specific androgen target tissues. Circulating SHBG levels are influenced by metabolic and hormonal factors, and they are reduced in obesity and insulin resistance, suggesting that SHBG may have a broader clinical utility in assessing the risk for cardiovascular diseases. Importantly, plasma SHBG levels are strongly correlated with testosterone concentrations, and in men, low testosterone levels are associated with an adverse cardiometabolic profile. Although obesity and insulin resistance are associated with an increased incidence of cardiovascular disease, whether they lead to abnormal expression of circulating SHBG or its interaction with androgen signaling remains to be elucidated. SHBG is produced mainly in the liver, but it can also be expressed in several tissues including the brain, fat tissue, and myocardium. Expression of SHBG is controlled by peroxisome proliferator-activated receptor γ (PPAR γ ) and AMP-activated protein kinase (AMPK). AMPK/PPAR interaction is critical to regulate hepatocyte nuclear factor-4 (HNF4), a prerequisite for SHBG upregulation. In cardiomyocytes, testosterone activates AMPK and PPARs. Therefore, the description of local expression of cardiac SHBG and its circulating levels may shed new light to explain physiological and adverse cardiometabolic roles of androgens in different tissues. According to emerging clinical evidence, here, we will discuss the potential mechanisms with cardioprotective effects and SHBG levels to be used as an early metabolic and cardiovascular biomarker in men.